The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1017/s0022381611000776
|View full text |Cite
|
Sign up to set email alerts
|

The Provision of Local Public Goods in Diverse Communities: Analyzing Municipal Bond Elections

Abstract: Scholars have shown that diversity depresses public goods provision. In U.S. cities, racial and ethnic divisions could seriously undermine investment. However, diverse cities spend significant amounts on public goods. We ask how these communities overcome their potential collective action problem. Using a new data set on more than 3,000 municipal bond elections, we show that strategic politicians encourage cooperation. Diversity leads officials to be more selective about requesting approval for investment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 40 publications
(46 reference statements)
3
55
0
1
Order By: Relevance
“…Thus, we might alternatively expect an increase in spending if diversity is accompanied by a greater push to fully serve each represented ethnic group. Some evidence consistent with this is provided by Rugh and Trounstine (2011). They find that diverse cities are more likely to propose spending packages that bundle public goods, which may be driven by an attempt to satisfy a diverse electorate.…”
Section: Introductionmentioning
confidence: 68%
“…Thus, we might alternatively expect an increase in spending if diversity is accompanied by a greater push to fully serve each represented ethnic group. Some evidence consistent with this is provided by Rugh and Trounstine (2011). They find that diverse cities are more likely to propose spending packages that bundle public goods, which may be driven by an attempt to satisfy a diverse electorate.…”
Section: Introductionmentioning
confidence: 68%
“…This behavior, repeatedly observed in the laboratory, is often cited as one of the primary reasons for the well-established finding that diversity is negatively correlated with public goods provision cross-nationally (Alesina and Zhuravskaya 2008;Enos and Gidron 2016;Habyarimana et al 2009). Scholars have drawn direct connections between local ethnic diversity and the willingness of voters to allocate funds for public goods, including schools (Alesina, Baqir, and Easterly 1999;Rugh and Trounstine 2011). Furthermore, research has shown that whites in the United States draw on negative stereotypes about African Americans when forming policy attitudes about benefits perceived to disproportionately target members of that racial group (Gilens 1999).…”
Section: Effects On White Policy Votingmentioning
confidence: 99%
“…Scholars have argued that ethnic diversity impedes the willingness of residents to tax themselves out of worry that the benefits of their investments will be captured by people much different than themselves, and diverted to policies they do not support (Alesina, Baqir, Easterly 1999;Alesina and Spolaore 1997;Easterly and Levine 1997;Glaser 2002;Habyarimana et al 2007;Poterba 1994;Putnam 2007;Rugh and Trounstine 2011). In addition, Alesina, Baqir, and Hoxby (2004) show that racial heterogeneity has historically been associated with local government fragmentation within U.S. local government and has posed a major barrier to government consolidation.…”
Section: The Rise Of Non-ad Valorem Assessmentsmentioning
confidence: 99%